2015
DOI: 10.3923/ajar.2015.123.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incubation Period of Phosphorus Fertilizer on some Properties of Sandy Soil with Low Calcareous Content, Southern Algeria

Abstract: Fertilization practices can contribute to modify the properties of the soils, in particular salinity and the pH of soils. The main goal of this study is to demonstrate the impact of the physicochemical properties changes related to applied phosphorus fertilizers on phosphorus availability in light textured soils having low calcareous content. A short-term incubation experiment during 105 days was carried out in field conditions. Three different phosphorus fertilizers (monoammonium phosphate, fosfactyl and sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
8
9
0
Order By: Relevance
“…In Tables 3, 4 and 5, soil available P levels decreased with the incubation time. This result is comparable with the results that reported by Anetor and Akinrinde (2007) and Deraoui et al (2015). Higher P levels were observed in the treatments where only TSP was added than in the treatments where only lime was added.…”
Section: Effect Of Lime and Phosphorous Treatments On Extractable Psupporting
confidence: 91%
See 1 more Smart Citation
“…In Tables 3, 4 and 5, soil available P levels decreased with the incubation time. This result is comparable with the results that reported by Anetor and Akinrinde (2007) and Deraoui et al (2015). Higher P levels were observed in the treatments where only TSP was added than in the treatments where only lime was added.…”
Section: Effect Of Lime and Phosphorous Treatments On Extractable Psupporting
confidence: 91%
“…In all soil samples where TSP was added, there was an increase in Borax, Olsen and Bray and Kurtz -1 extractable P levels and that was in agreement with other works, in-cluding that of Waigwa et al (2003) and Deraoui et al (2015). In the limed soils with no P addition, too resulted in a small increase in P concentration.…”
Section: Effect Of Lime and Phosphorous Treatments On Extractable Psupporting
confidence: 91%
“…The mineral fertilizer, especially Hoagland solution, will contain free phosphates and it will, upon application, be available at once. Free phosphates on the other hand can easily become adsorbed, immobilized or leached out of reach, in a time dependent manner, and the longer it is in solution in high amounts the larger the portion that is unavailable for the plant (Shen et al, 2011;Deraoui et al, 2015;Demiraj et al, 2017). Living algae contain a metabolic active P supply, in form of phosphate contained in the cytosol (Solovchenko et al, 2016), The figure states our hypothesis on how algal biomass will release phosphate from different bound forms (A), including inorganic P, organically bound P and polyphosphates.…”
Section: Availability Of Algal P Is Temporally and Spatially Different From Mineral Pmentioning
confidence: 99%
“…Phosphate fertilizer significantly increased pH from 0 to 30 days in the soil. The dissolution of mineral fertilizers in the soil has various effects on soil properties, including pH, whereas P fertilizers tend to decrease pH values (Boukhalfa-Deraoui et al, 2015). Our results indicated that biochar increased the pH of the soil (Jiang et al, 2015).…”
Section: Discussionmentioning
confidence: 66%